Biopotential Features and Pesticidal Study of Cascabela peruviana, Nerium oleander, and Mimusops elengi against Armyworm Spodoptera litura (Noctuidae: Lepidoptera) and Pod Borer Larvae of Helicoverpa armigera (Noctuidae: Lepidoptera): Biopotential Features and Pesticidal Study of Cascabela peruviana, Nerium oleander, and Mimusops elengi against Armyworm Spodoptera litura (Noctuidae: Lepidoptera) and Pod Borer Larvae of Helicoverpa armigera (Noctuidae: Lepidoptera) - Palanisamy, K. (International Journal of Pharmaceutical & Biological Archive, 2019)
To study the report, the different solvents of methanol, ethyl acetate, chloroform, and acetone for Cascabela peruviana (C. peruviana), Nerium oleander (N. oleander), and Mimusops elengi (M. elengi) were used the experimental analysis in pest control of most dangerous notorious Lepidopteran pests of Spodoptera litura (S. litura) and Helicoverpa armigera (H. armigera). The antifeedant activity of C. peruviana against S. litura 98.6%, H. armigera 94.6%, N. oleander against S. litura 94.2%, H. armigera 90.8% and M. elengi against S. litura 92.8%, H. armigera 86.4%. Lethal concentration 50 (LC50) and LC90 values of C. peruviana against S. litura, H. armigera the values are S. litura (LC50 = 88.3 and LC90 = 204.91) and H. armigera (LC50 = 103.19 and LC90 = 232.10), N. oleander against S. litura (LC50 = 102.10 and LC90 = 228.01) and H. armigera (LC50 = 121.10 and LC90 = 254.69) and M. elengi against S. litura (LC50 = 120.55 and LC90 = 250.43). The oviposition deterrent activity of C. peruviana against S. litura 90.8%, H. armigera 86.2%, N. oleander against S. litura 88.6%, H. armigera 82.8% and M. elengi against S. litura 78.2%, H. armigera 73.6%. When same species it is proof that methanol extract of C. peruviana, N. oleander, and M. elengi plant flower extracts was most effective insecticidal activity of armyworm S. litura and pod borer larvae of H. armigera. Performance of maximum antifeedant activity, lethal activity, and oviposition deterrent activity recorded in the methanol extract of C. peruviana than could be utilized in pest control program.